Personal Taxes and Firm Skill Hiring: Evidence from 27 Million Job Postings - Campello, Murillo; Gao, Janet; Xu, Qiping (Management Science, 2024)
Using big data on U.S. job postings, we show that firms increase skill requirements when hiring workers in states that cut personal income taxes. We trace a significant driver of this effect to companies’ reallocation of skilled job postings across states based on tax differentials. The tax-induced upskilling is observed within occupations and is more pronounced for high-skill positions within firms. It is accompanied and amplified by concurrent increases in information technology expenditures at local-level establishments. In characterizing the mechanism at play, we show that job upskilling is triggered by tax changes affecting middle- and upper middle-class workers. It is pronounced for high-growth firms, for firms in tradable industries, and in urban areas, but it is mitigated among profitable firms. A narrative-based analysis helps us establish causal inferences. This paper was accepted by Victoria Ivashina, finance. Supplemental Material: The data files and online appendix are available at https://doi.org/10.1287/mnsc.2022.01211 .